Collaboration between Sharia Banks and FinTech: Ethical Challenges and Human Resource Readiness - Fajar Budi Utomo; Yovi Kusumadani; Linda Jayanti; Nur Aeni; Agnes Jevi Rialita (Nuban Jagadhita Centre, 2026)
Objective: This article aims to analyze the collaboration between Islamic banks and FinTech, with particular emphasis on ethical challenges and human resources (HR) readiness to support the sustainability of the digital Islamic finance ecosystem. The study explores how technological innovation can be aligned with Sharia principles while maintaining institutional integrity and competitiveness. Method: This study employs a descriptive qualitative approach using a literature review method. Data were collected from Indonesian-language academic journals and scholarly publications related to Islamic banking, FinTech, Islamic business ethics, digital transformation, and human resource development. The collected literature was analyzed thematically to identify major trends, challenges, and opportunities in the integration of Islamic banking and financial technology. Results: The findings reveal that collaboration between Islamic banks and FinTech contributes significantly to improving service efficiency, accelerating financial inclusion, expanding access to Sharia-compliant financial services, and enhancing customer experience. Nevertheless, several challenges remain, including ethical gaps in digital transactions, the risk of Sharia non-compliance, inadequate digital literacy, limited technological capabilities, and insufficient understanding of fiqh muamalah among the human resources involved in digital financial services. Implication: These findings highlight the need to strengthen Islamic business ethics, improve digital competencies, and provide continuous fiqh muamalah training for human resources. Furthermore, Sharia regulation and supervisory mechanisms should be adaptive and responsive to technological developments. Novelty: This article identifies a gap in previous studies by demonstrating that the success of digital collaboration depends not merely on technological adoption but also on the balanced integration of Islamic ethical values, HR readiness that combines digital literacy and fiqh muamalah competencies, and adaptive Sharia governance within the evolving digital financial ecosystem.